Education for sustainability through a photography competition - Scott, Rowena (Adver, SUSTDE, 2014)
This article describes the development and history of a sustainability photography competition. From its simple beginnings as an environmental officer's idea, an environmental sustainability photography competition began in just one university. Now hosted by Australasian Campuses Towards Sustainability (ACTS), finalist entries are viewed on a public website gaining international attention. A purpose of the article is to demonstrate the diversity of views of sustainability by displaying the winning entries from 2013 and 2012. It is anticipated that readers may replicate these ideas in creative arts and across disciplines throughout primary, secondary and other high education institutions, community groups and diverse organisations.